Talk and Die Syndrome: An Unending Mystery - Stanly, Steffy; Tejasree, Thota; Nandini, VLD; Ponnusankar, S (Indian Journal of Pharmacy Practice)
The Traumatic Brain Injury is one of the most leading cause of the increased mortality and morbidity rate in the current populace, which induces sub-dural hematoma, hence while talking itself the person will die and so nick named as ‘Talk and Die Syndrome’. Interesting field in neurology, with very rare incidence rate and CT scan plays a golden role in the diagnosis of Traumatic Brain Injury.
Keywords: Talk and die syndrome; Epidural hematoma; Traumatic brain injury; Natasha case; Treatment